Application of the high-flow nasal cannula in patients with acute respiratory distress syndrome - Stergiopoulou, Evgegia; Niki , Pavlatou (Health & Research Journal, 2025)
Background: Acute respiratory distress syndrome (ARDS) is an acute inflammatory pulmonary process, which leads to protein-rich non-hydrostatic pulmonary oedema. It causes persistent hypoxemia, increases lung "stiffness" and impairs the lung's ability to excrete carbon dioxide. With the advent of the COVID-19 pandemic, many patients suffering from ARDS could not avoid falling ill. However, in many cases, the time from the onset of disease symptoms to the development of full-blown ARDS differed from that observed in ARDS caused by other underlying conditions. Based on the available data, ARDS associated with COVID-19 does not appear to exhibit a more rapid or severe progression of lung damage compared to ARDS from other causes. Treatment approach: Supplemental oxygen therapy is one of the most commonly prescribed interventions used by clinicians when treating hypoxic acute care patients. This supplement often comes in the form of a low-flow nasal cannula (LFNC). The nasal cannula is an open system that provides low flow and low oxygen. Particularly in patients with COVID-19, HFNO has been shown to create a more uniform transmission of pressure and distribution of ventilation in the alveoli, compared to invasive mechanical ventilation. Results: As a result, the probability of overdistension of open alveoli, together with the opening of closed alveoli, is reduced in a heterogeneous lung affected by SARS-COV-2. In normal breathing, about 1% of the air a person inhales is made up of the air exhaled in the previous breath. The result is that part of the exhaled CO2 is respired. However, the use of high-flow nasal oxygen (HFNO) facilitates the delivery of heated, humidified oxygen at high flow rates, effectively flushing out CO₂ from the anatomical dead space in the trachea and bronchi, thereby enhancing gas exchange. This reduces the anatomical dead space and respiration of CO2, promoting its elimination. Conclusions As a result, HFNO has been shown to be effective in treating hypercapnia-induced respiratory failure. The purpose of the present study is to investigate the therapeutic effect after the application of the high-flow nasal cannula in patients with acute respiratory distress syndrome.